Receptores GPS de três precisões e estação total na caracterização de cotas básicas para projetos rurais - Rodrigues, Vilmar A. [UNESP]; Cardoso, Lincoln G. [UNESP]; Gomes, Luciano N. [UNESP]; De Barros, Zacarias X. [UNESP]; Campos, Sérgio [UNESP] (Elsevier, 2006)
The objective of this work was to compare cotas of polygonal vertices, through three different receiving GPS, using as reference a total station. The data were obtained in a closed polygonal, being treated later by the software Topograph. The cotas obtained by the three receivers were confronted with those calculated by means of the application of the test, being verified that the cotas were satisfactory for the equipment GPS Geodesic Trimble® 4600 LS. For the equipment GPS Trimble® topographical model PRO XR, the cotas weren't totally satisfactory, but possible of being considered in preliminary projects. For the navigation equipment GPS Garmin® 12 XS the cotas were shown unacceptable for the studied purpose.
Receiving GPS of three precision and total station in the characterization of basic cota for rural projects
Keywords: Cotas; GPS; Total station